Lots of Selves, some rebellious: Developing the Self Discrepancy Model for Language Learners. (August 2016) - Lanvers, Ursula
Abstract: This article develops a new language learning motivation model, which is, like the currently dominant model by Dörnyei, based on Higgins' (1987) Self Discrepancy Theory . Increasing evidence of 'non-fit' of Dörnyei's model, especially (but not solely) from language learners with English as a first language, let to the author revisiting Higgins' original, which had more complex delineation of different Selves that adopted by Dörnyei. After critically reviewing the body of literature suggesting 'non-fit' of Dörnyei's model, a model with Higgins' original delineations of Selves is proposed and adapted to the language learning context, and then applied on novel data from two different learner groups with English as first language: mature university and adolescent school students. The proposed S elf Discrepancy Model for Language Learners contributes to solutions of several problems raised in current discussion of language learner motivation: it provides a better fit of data seemingly incompatible with Dörnyei's model, especially a learner type labelled 'rebellious', offers a better embedding of a range of contextual influences on motivation, and facilitates developmental perspectives on language learner motivation. The empirical data delivers on the first two goals, and offers pathways regarding the last. Highlights: Despite its undisputable success, problems remain regarding Dörnyei's L2 Motivational Self System, in particular regarding the Other dimension, as well as locating wider contextual influences within the model. The Self Discrepancy Model for Language Learners offers a novel answer to these challenges, first by re-instating the more complex Self-delineations from Higgins, secondly by adapting these to language learner contexts. The model also offers developmental perspectives on the internalization of externally-determined motivation in young learners.